Science is a Girl Thing. An Educational Strategy for Gender Equality (2019)
Given the low participation of women in science studies, Professor Adriana Paola Gonzales questions how to make it known that science is also something for women and so with the help of women who have come a long way in the topic of science gave talks at clemency school in Caycedo so that girls would cheer up from there came projects and more schools came together to create that awareness and potentialize the women's power in science.